Current Account Dynamics and the Housing Cycle in Spain - Eric Mayer; Daniel Maas; Sebastian Rüth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate the negative correlation between housing markets and the current account in Spain. By employing robust sign restrictions, which we derive from a DSGE model for a currency union, we analyze the effects of Spanish pull and Eurozone push factors in a mixed frequency VAR framework. Savings glut, risk premium, and housing bubble shocks are capable of generating the negative co-movement of housing markets and the current account in the data. In contrast, and counterfactual to the housing boom, financial easing shocks in Spain predict a decline in, both, residential investment and house prices. Among the four identifed shocks, savings glut shocks have most explanatory power for real house prices, whereas risk premium shocks account for most of the variation in residential investment. Financial easing shocks explain fluctuations to a similar extend as savings glut and risk premium shocks, while housing bubble shocks explain slightly less variance in the data.
Keywords: E32; F32; F45; 330